2018
DOI: 10.3174/ajnr.a5690
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of New MS Lesions during Follow-Up Using an Automated MR Coregistration-Fusion Method

Abstract: Our study showed that an automated coregistration-fusion method was more sensitive for detecting new high-signal T2 lesions in patients with MS and reducing reading time. This method could help to improve follow-up care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
2
17
2
Order By: Relevance
“…23,24 Semiautomated imaging represents a growing field of MS and radiology research, with methods ranging from assisted lesion assessment to brain volumetric analysis. 6,19,25 Similar growth is seen with an extension of computer-assisted detection called "radiomics," which converts images to minable data for deep learning. 26 Image coregistration is a crucial component of traditional MR imaging comparison.…”
Section: Figmentioning
confidence: 86%
See 2 more Smart Citations
“…23,24 Semiautomated imaging represents a growing field of MS and radiology research, with methods ranging from assisted lesion assessment to brain volumetric analysis. 6,19,25 Similar growth is seen with an extension of computer-assisted detection called "radiomics," which converts images to minable data for deep learning. 26 Image coregistration is a crucial component of traditional MR imaging comparison.…”
Section: Figmentioning
confidence: 86%
“…Semiautomated imaging software has shown great promise in the field of MS disease monitoring. [17][18][19] Earlier studies of VT concluded that it allowed higher lesion detection with improved interreader reliability and decreased reporting times when used by readers of all radiology training levels (ie, ranging from medical student to fellowship-trained neuroradiologist) compared with their performance using CSSC. 8,9,14 The main caveats of prior research in this area, however, included the retrospective design, artificial research conditions, and/or relatively small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for the purpose of follow‐up imaging of heteromorphic brain tumors as astrocytoma, for which longitudinal evaluation of disease is paramount, these tools have not been systematically investigated yet. Our hypothesis was that an automated coregistration approach could yield comparable advantages for astrocytoma follow‐up, as previously shown for MS patients . Hence, the study purpose was to compare diagnostic accuracy, required reading time, and diagnostic certainty between longitudinal assessment of FLAIR sequences with and without automated coregistration in patients with low‐ or high‐grade astrocytoma.…”
mentioning
confidence: 91%
“…Assessing repetitive MRI examinations, however, is time‐consuming, and comparability may be hampered by discrepant acquisition protocols or the use of heterogeneous MRI scanners. Thus, techniques for subtraction and automated coregistration of such repetitive follow‐ups have been developed and reported to be useful, particularly for follow‐up of multiple sclerosis (MS) with high lesion burden . It was reported that along with the use of these tools, diagnostic accuracy could be increased, while required reading was reduced …”
mentioning
confidence: 99%